Insight into the PmrB structures of colistin-resistant Gram-negative bacteria through the multi-template ligand-guided homology modeling and in silico mutagenesis - Anuwongcharoen, Nuttapat; Phanus-umporn, Chuleeporn; Chatupheeraphat, Chawalit; Weakwiweak, Kamonlak; Kaewsai, Noramon; Eiamphungporn, Warawan (PeerJ, 2025)
The increasing prevalence of colistin-resistant Gram-negative bacteria necessitates the development of novel therapeutic strategies. PmrB, a histidine kinase involved in colistin resistance, represents a promising drug target. However, the absence of experimentally resolved PmrB structures limits structure-based drug design efforts. This study employed a multi-template, ligand-guided homology modeling approach to construct full-length PmrB models for four pathogens: Acinetobacter baumannii, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa. The resulting models demonstrated high structural integrity, with over 95% of residues located in favored regions and QMEANDisCo global scores ranging from 0.55 to 0.57. Molecular docking simulations guided the selection of representative ligand-bound states for adenosine triphosphate (ATP)-binding site prediction and yielded superior docking scores compared to models generated by AlphaFold, I-TASSER, and SWISS-MODEL. Molecular dynamics (MD) simulations and Molecular Mechanics Generalized Born Surface Area (MM/GBSA) analysis confirmed the stability and binding affinity of the PmrB–ATP complexes, with ΔG values ranging from −27.72 to −47.71 kcal/mol. In silico mutagenesis revealed that the T246A and L344P mutations in K. pneumoniae enhanced ATP binding affinity and protein stability, potentially contributing to colistin resistance. Analysis of the PmrB–ATP complexes identified both conserved and species-specific interactions. This research provides valuable structural models and mechanistic insights into PmrB, supporting future structure-based drug design and the development of novel interventions against colistin-resistant infections.
Keywords: PmrB; Colistin resistance; Homology modeling; Molecular docking; Molecular dynamics; Structure-based drug design